The Arabidopsis Tellurite resistance C protein together with ALB3 is involved in photosystem II protein synthesis. (26th March 2014) - Schneider, Anja; Steinberger, Iris; Strissel, Henning; Kunz, Hans‐Henning; Manavski, Nikolay; Meurer, Jörg; Burkhard, Gabi; Jarzombski, Sabine; Schünemann, Danja; Geimer, Stefan; Flügge, Ulf‐Ingo; Leister, Dario
Summary Assembly of photosystem II (PSII) occurs sequentially and requires several auxiliary proteins, such as ALB3 (ALBINO3). Here, we describe the role of the Arabidopsis thaliana thylakoid membrane protein Tellurite resistance C (AtTerC) in this process. Knockout of AtTerC was previously shown to be seedling‐lethal. This phenotype was rescued by expressing TerC fused C–terminally to GFP in the terc–1 background, and the resulting terc–1TerC–GFP line and an artificial miRNA‐based knockdown allele (amiR‐TerC) were used to analyze the TerC function. The alterations in chlorophyll fluorescence and thylakoid ultrastructure observed in amiR‐TerC plants and terc–1TerC–GFP were attributed to defects in PSII. We show that this phenotype resulted from a reduction in the rate of de novo synthesis of PSII core proteins, but later steps in PSII biogenesis appeared to be less affected. Yeast two‐hybrid assays showed that TerC interacts with PSII proteins. In particular, its interaction with the PSII assembly factor ALB3 has been demonstrated by co‐immunoprecipitation. ALB3 is thought to assist in incorporation of CP43 into PSII via interaction with Low PSII Accumulation2 (LPA2) Low PSII Accumulation3 (LPA3). Homozygous lpa2 mutants expressing amiR‐TerC displayed markedly exacerbated phenotypes, leading to seedling lethality, indicating an additive effect. We propose a model in which TerC, together with ALB3, facilitates de novo synthesis of thylakoid membrane proteins, for instance CP43, at the membrane insertion step.